MENGUNGKAP SEJARAH DAN MOTIF BATIK SEMARANG SERTA PENGARUH TERHADAP MASYARAKAT KAMPUNG BATIK TAHUN 1970-1998 - Afreliyanti, Susi (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2014)
Kampung Batik Semarang in Rejomulyo Village, District East Semarang. Kampung Batik Batik is the biggest producer in Semarang. In a research report stating that many natives in Semarang livelihood in the batik industry sectors. 1970 - 1998 A lot of events happening in the world of Batik Semarang. From the early generation of batik village until the monetary crisis lunge keeksisan batik dyeing semarang, addition appears also Effect of the batik batik village semarang to society. The results showed that this is the place Kampung Batik largest batik producer disemarang.Tahun 1970 appeared the famous Batik company named